2016
DOI: 10.1063/1.4960768
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer borophene electrode for effective elimination of both the Schottky barrier and strong electric field effect

Abstract: The formation of Schottky barriers between 2D semiconductors and traditional metallic electrodes has greatly limited the application of 2D semiconductors in nanoelectronic and optoelectronic devices. In this study, metallic borophene was used as a substitute for the traditional noble metal electrode to contact with the 2D semiconductor. Theoretical calculations demonstrated that no Schottky barrier exists in the borophene/2D semiconductor heterostructure. The contact remains ohmic even with a strong electric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
0
16
2
1
Order By: Relevance
“…As an alternative, two-dimensional (2D) boron or borophene is a recently proposed monolayer material that has been predicted to display metallic properties, 1215 and form Ohmic contacts to 2D semiconductors, greatly enhancing the performance of electronic devices. 16…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, two-dimensional (2D) boron or borophene is a recently proposed monolayer material that has been predicted to display metallic properties, 1215 and form Ohmic contacts to 2D semiconductors, greatly enhancing the performance of electronic devices. 16…”
Section: Introductionmentioning
confidence: 99%
“…The electronic, optical and thermodynamic properties were investigated for the borophene26. It was demonstrated that there is no Schottky barrier between the metallic borophene and other two-dimensional semiconductors, which is useful for the construction of two-dimensional electronic devices with enhanced performance27. Borophene has negative Poisson’s ratio in the out-of-plane direction and the in-plane directions resulting from its puckered configuration7282930.…”
mentioning
confidence: 99%
“…Borophene can exist in many different allotropes, all, while metallic, displaying distinct features of the band structure; [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and has been predicted to form Ohmic contacts with other 2D semiconductors, suggesting that it can be a tunable monolayer metal. 27 Additionally, several reports have predicted phonon-mediated superconductivity in borophene, [22][23][24][25][26] which is very sensitive to carrier doping and strain, 25,26 and extremely low lattice thermal conductivity 28 compared with carbon-based materials 29 . To take advantage of borophene as a nano-optoelectronic material, it is necessary to understand its fundamental, intrinsic properties.…”
Section: Introductionmentioning
confidence: 99%